2019
DOI: 10.1128/iai.00787-18
|View full text |Cite
|
Sign up to set email alerts
|

Shiga Toxin Type 1a (Stx1a) Reduces the Toxicity of the More Potent Stx2a In Vivo and In Vitro

Abstract: Shiga toxin (Stx)-producing Escherichia coli (STEC) causes foodborne outbreaks of bloody diarrhea. There are two major types of immunologically distinct Stxs: Stx1a and Stx2a. Stx1a is more cytotoxic to Vero cells than Stx2a, but Stx2a has a lower 50% lethal dose (LD50) in mice. Epidemiological data suggest that infections by STEC strains that produce only Stx2a progress more often to a life-threatening sequela of infection called hemolytic-uremic syndrome (HUS) than isolates that make Stx1a only or produce bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
(41 reference statements)
2
20
0
Order By: Relevance
“…Furthermore, Stx2a cannot compete with Stx1a for binding to Gb3 in detergent-resistant membranes (53). This observation is consistent with our intoxication assay, which demonstrated that a 100-fold molar excess of Stx2a cannot outcompete Stx1a, and with published work demonstrating that the B subunit from Stx1a reduces the toxicity of Stx2a (48). The bimodal response to Stx2 subtypes thus appears to result from two linked events that limit the cytosolic pool of Stx2 in comparison to Stx1a, namely, (i) relatively weak overall binding to the target cell, and (ii) a weaker interaction than Stx1a with the detergent-resistant membranes that are required for toxin transport to the ER and cytosol.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, Stx2a cannot compete with Stx1a for binding to Gb3 in detergent-resistant membranes (53). This observation is consistent with our intoxication assay, which demonstrated that a 100-fold molar excess of Stx2a cannot outcompete Stx1a, and with published work demonstrating that the B subunit from Stx1a reduces the toxicity of Stx2a (48). The bimodal response to Stx2 subtypes thus appears to result from two linked events that limit the cytosolic pool of Stx2 in comparison to Stx1a, namely, (i) relatively weak overall binding to the target cell, and (ii) a weaker interaction than Stx1a with the detergent-resistant membranes that are required for toxin transport to the ER and cytosol.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, Stx2a does not appear to effectively compete with Stx1a for binding to functional receptors on the target cell. A recent study documented the reduced potency of Stx2a in cell culture and animal models when mixed with the Stx1a B subunit (48), but our current work-which was only possible because of the different population responses to Stx1a versus Stx2a-provides the first experimental evidence that the Stx1a holotoxin can outcompete Stx2a in a cell culture model of intoxication.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Our laboratory previously demonstrated in co-intoxication studies that Stx1a reduces Stx2a mediated toxicity in vivo particularly when more Stx1a than Stx2a is administered (Russo et al, 2016). We also recently found that the presence of Stx1a reduces the morbidity in Str-treated mice after infection with an STEC strain that makes both Stx1a and Stx2a (Petro et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Another distinct feature is the presence of stx1a in most of the Australian isolates. Stx1a has been shown to have antagonistic effects against Stx2a toxicity, shown in both in vitro and in vivo models, where Stx2a alone appears to be more potent (Petro et al, 2019). This reduction in Stx2a toxicity is potentially due to the stronger receptor binding affinity to the globotriaosylceramide (Gb3) receptor of the B subunit of Stx1a, blocking out the binding of Stx2a to the Gb3 receptor (Head et al, 1991;Tesh et al, 1993;Zumbrun et al, 2010;Karve and Weiss, 2014;Russo et al, 2014;Cherubin et al, 2019).…”
Section: Core Genome Analysismentioning
confidence: 99%